Enhancing the photocatalytic activity of ZnO nanoparticles for efficient rhodamine B degradation by functionalised graphene nanoplatelets - Worajittiphon,P. (Elsevier Limited, 2015)
© 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved. Amine-functionalised graphene nanoplatelets were decorated with ZnO nanoparticles using a hydrothermal method to improve the photocatalytic activity of the ZnO in dye degradation. Nanocomposite characterisations using X-ray diffraction, Raman spectroscopy and transmission electron microscopy reveal effective interactions between the two constituents. The nanocomposite structure contributes to a high specific surface area, which increases the number of active sites, thus improving the light harvesting ability and the electron transfer efficiency and, subsequently, increasing the photogenerated electron-hole pair separation rate, as shown by the UV-vis diffuse reflectance spectroscopy and photoluminescence results. The resultant enhancement in the photocatalytic activity under ultraviolet light is demonstrated via rhodamine B degradations of up to 98.16% within 40 min, an exceptional degradation rate of 0.138 min-1. The nanocomposite could alternatively be a new class of photocatalyst materials with potential uses in the remediation of polluted water.